The Effect of Curcuma Extract Emulsion as an Amara on Ghrelin Hormone Profiles and Increased Feed Consumption in Male Rats - Riyadatus Solihah; Umar, Rizal (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2026)
Background : Curcuma (Curcuma xanthorrhiza Roxb.) contains curcuminoids and essential oils that aid bile and pancreatic function, thereby improving food absorption in the intestines and increasing appetite. However, the underlying biological mechanisms of the hormones that regulate hunger and satiety have not been extensively reported. This study aims to analyze the appetite-suppressing mechanism of curcuma rhizome extract emulsion by observing changes in ghrelin hormone levels in male Wistar rats. Methods : This study was an experimental study using a post-test only control group design. The test animals were divided into four groups: negative control (distilled water), and three treatment groups that received curcuma extract emulsion at different concentrations (10%, 20%, and 30%). The treatment was administered orally for 21 days. The parameters obtained included ghrelin levels in serum, which were analyzed using the ELISA method, while additional parameters included daily feed intake and weight change. The data obtained were analyzed using normality and homogeneity tests, followed by one-way ANOVA and post-hoc tests. Results: This study shows that administration of curcuma extract emulsion can enhance the effects of amara, as seen from increased feed intake and body weight, and by increased ghrelin levels when compared to the control. Conclusions: This study concluded that curcuma functions as an appetite stimulant through hormonal pathways, which has the potential to be developed as a phytopharmaceutical candidate to increase appetite through a mechanism-based approach.